The philosophy of love in The Ring of the Dove by Ibn Hazm and its role in promoting values. - Razzaq, Prof. Dr. Hossam Saadi Abdul Razzaq Abdul; Al-Dulaimi, Prof. Dr. Khamees Faza' Umayr Al-Dulaimi; Aziz, Prof. Dr. Ahmed Safaa Abdul Aziz Abdul (Sulaimani Journal for Humanities, 2026)
Abstract: The research aims to reveal the philosophical and intellectual features of the concept of love and the ideas and views related to it in Ibn Hazm Al-Andalusi through his book, The Ring of the Dove, in which he embodied the meanings of human feelings. In this research, we relied on the analytical method, drawing on previous studies and what we reached through reading and contemplation.
Keywords: love; indication; philosophy; Islam; poetry